ANALISIS PERBANDINGAN METODOLOGI BNPB DAN TSVI UNTUK PENILAIAN RISIKO TSUNAMI DI ACEH JAYA, INDONESIA - Vidya, Dinda Puspa; Ossy Maulita Budiawati; Ane Arifa Ditami; Riantini Virtriana (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2025)
COMPARATIVE ANALYSIS OF BNPB AND TSVI METHODOLOGIES FOR TSUNAMI RISK ASSESSMENT IN ACEH JAYA, INDONESIA Aceh Province is considered to be a high-risk area for tsunami susceptibility, a consequence of its geographical proximity to the Sumatra subduction zone. The objective of this study is to compare two methods of tsunami risk assessment, namely the BNPB's official Kajian Risiko Bencana (KRB) framework and the Tsunami Spatial Vulnerability Index (TSVI) method in Aceh Jaya District. The BNPB's KRB approach integrates hazard and vulnerability components using criterion-based analysis in a Geographic Information System (GIS), while the TSVI employs Spatial Principal Component Analysis (SPCA) to analyse large geospatial data, including satellite images, population grids, and economic center location points. The results demonstrate significant discrepancies in the spatial distribution of high-risk zones in the final tsunami risk map derived from each method, due to the different paradigms of susceptibility concept utilisation. The findings also shown that TSVI method can yield additional insights that are not obtained from BNPB's KRB method, concerning the primary contributors to vulnerability in the study area. This study demonstrates the potential of TSVI as a complementary tool to conventional disaster risk assessment, and emphasise the importance of integration between institutional frameworks and data-driven approaches to support more responsive and more contextualised disaster mitigation planning.